Educação financeira no ensino médio: uma proposta para as aulas de matemática - Moraes, Aline Reissuy de (2019)
This dissertation is at methodological theory elements line research for Science and Mathematics teaching seeks to show possible association aspects of financial education with the financial Mathematics classes at second grade to give the students of this teach level knowledge can give them more autonomy and security in relation to their financial lives. It is a qualitative research based on Paulo Freire’s theory because for this writer should the ideas agreement in respect to a world vision based on research, common sense, curiosity and hope main regard to autonomy, great and democratic education. It was developed a didactic sequence based on a didactic engineering methodology research. The study was developed in three classes of third grade of second grade of a state wide public school in Carazinho/RS city. The didactic sequence resulting from this study generated a Guide for Financial Education in High School classes, as an educational product, available at the following address http://educapes.capes.gov.br/handle/capes/559604>, for teachers who wish to make use of it in their classroom, which accompanies this dissertation. Analyzing if the goals were achieved used the diary classes as the research teacher as the students, besides questions asked for students. The databases collected and analyzes showed the importance to work the subject with teenagers students giving them knowledge to have a more peaceful financial life.